Existence of time periodic solutions for one-dimensional Newtonian filtration equation with multiple delays - Ying Yang; Jingxue Yin; Chunhua Jin (Electronic Journal of Qualitative Theory of Differential Equations, 2010)
In this paper, we study one-dimensional Newtonian filtration equation including unbounded sources with multiple delays. The existence of nonnegative non-trivial time periodic solutions will be established by the Leray-Schauder fixed point theorem based on some suitable Lyapunov functionals and some a priori estimates for all possible periodic solutions.